The creation of the academic podcast as a means of transforming football knowledge (Impetus, 2025)
This article describes the process of creating and producing an academic-sports podcast based on scientific evidence and the expertise of professionals specializing in technical, tactical, psychological, and medical structures. The methodology begins with an in-depth investigation of each structure, followed by the organization of content into scripts for specific chapters. Each chapter presents a thorough analysis supported by scientific evidence and expert interviews. This methodology provides a comprehensive and multidisciplinary approach to addressing football from different perspectives, aiming to strengthen and enrich the knowledge of both sports enthusiasts and professionals.
Keywords: Football; education; communication; pedagogy